Expression of Matrix Metalloproteinases-8 and Myeloperoxidase in Pulp Tissue after Pulpotomy with Calcium Silicate Cements - Nayara Nery de Oliveira Cunha; Marina Azevedo Junqueira; Leopoldo Cosme-Silva; Laís da Silveira Terra Santos; George Augusto Veloso de Oliveira; Rafael Tobias Moretti Neto; Denismar Alves Nogueira; Maísa Ribeiro Pereira Lima Brigagão; Ana Beatriz da Silveira Moretti (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the pulp tissue of rat molars after pulpotomies with mineral trioxide aggregate (MTA), BiodentineTM (BDT) and calcium hydroxide (CH) mixed with sterile saline solution (24 hours, 72 hours, 7 days and 15 days), through correlating MPO activity with active neutrophils and MMP8 activity with tissue remodeling. Material and Methods: Thirty-eight Wistar rats were randomly distributed into groups (control, I (MTA gray), II (BDT), and III (CH)) and subdivided according to the study period of 24 hours, 72 hours, 7 days or 15 days after pulpotomy. MMP8 activity was assessed through fluorescence technique, and MPO activity was determined using the MPO assay. Results: A gradual decrease of MPO and MM8 activity occurred in the group MTA over the experimental periods (p<0.05). Groups BDT and CH exhibited an increase in the activity at 7 and 15 days (p<0.05). Conclusion: MTA demonstrated a decrease in the values of MPO e MMP8. BDT and CH showed high neutrophilic and collagenase activity over the experimental periods.